Effect of 8 Weeks of Grip Strength Training on Adolescent Sprint Swimming: A Randomized Controlled Trial - Khaled Abdullah Alshdokhi; Carl James Petersen; Jenny Claire Clarke (Sapientia Publishing Group, 2020)
OBJECTIVES Grip strength positively correlates with faster sprint swimming performance in both master and elite level swimmers. But it remains unknown whether improving grip strength improves swim performance. Our objective was firstly to increase grip strength and secondly to determine if improved grip strength results in faster backstroke and freestyle sprint swimming performance. METHODS Using a randomised, control trial design 26 adolescent swimmers were randomly divided into either a swimming only Control group (n=9, age 11.5 ± 1.6 y; 6 male, 3 female) or one of two grip strength training groups: Powerball (n=9, age 11.5 ± 1.6 y, 6 male, 3 female) or Stressball (n= 8, age 11.6 ± 1.6 y, 5 male, 3 female). The Powerball (Powerball and Power Gripper devices) and Stressball (Stressball and Skrunch ball) groups completed a grip strength training program (4x/week for 8 weeks) in addition to their normal swimming training (4 hours per week). Pre and post the training intervention, isometric grip strength was measured using a mechanical hand dynamometer (Lafayette Instrument, Lafayette, IN) while 50 m freestyle and 100 m backstroke short-course swimming time trials were also undertaken. RESULTS Over 8 weeks, all groups improved their maximal grip strength with moderate to large changes (Powerball 30 ± 12%, ES=1.70; Stressball 36 ± 22%, ES=1.07; Control 35 ± 12%, ES=0.79). There were no statistically significant changes for any group in the 100 m backstroke (P>0.05), but significant (P<0.05) small improvement in the Powerball (4.1 ± 5.6%, ES=0.26) and Stressball groups (3.4 ± 3.4%, ES=0.24) during 50 m freestyle. There were no significant between group changes for any variable. CONCLUSIONS Grip strength improved but failed to improve 100 m backstroke performance. Improving grip strength may contribute towards faster 50 m freestyle swim performance in this adolescent age group.